John Bell papers - Bell, John, 1797-1869.
Volume containing correspondence, speeches, and Bell's reports in congress. Includes material on patronage in Tennessee, national politics, and Bell's candidacy for president in 1860. Correspondents include Neill Smith Brown, Frederick Steidinger Heiskell, Washington Hunt, and Balie Peyton.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
U.S. representative and senator from Tennessee, and U.S. secretary of war.
Collection material in English.
Keywords: Brown, Neill Smith, -- 1810-1886 -- Correspondence; Heiskell, Frederick Steidinger, -- 1786-1882 -- Correspondence; Hunt, Washington, -- 1811-1867 -- Correspondence; Peyton, Balie, -- 1803-1878 -- Correspondence; United States. -- Congress. -- Senate; Patronage, Political -- Tennessee; Presidents -- United States -- Election -- 1860.; Tennessee -- Politics and government -- To 1865.; United States -- Politics and government -- 1815-1861.; Cabinet officers; Lawyers; Senators, U.S. Congress -- Tennessee